Study of tourism suitability and carrying capacity for fisheries-based ecotourism development in Jatigede Reservoir, West Java, Indonesia - Sulastri prihandini; Zahidah Dahalan; M. Candra w. Arief; Heti herawati; Carolyn m. Payus; Siti Irbah Anuar (Journal of Sustainability Science and Management, 2024)
A reservoir is a multipurpose dam. The Jatigede reservoir in Sumedang Regency, West Java Province, Indonesia has excellent potential as a Fisheries-based Ecotourism (FbE) development due to its sufficiently wide inundation area, the availability of fish and marine resources, wealth of natural scenery and strategic location. Currently, Jatigede Reservoir is a well-known natural tourism destination and research study area; however, minimal studies have been conducted on the environmental aspects of tourism. This study aims to determine the ecological potential of Jatigede Reservoir as a Fisheriesbased Ecotourism (FbE) destination and its suitability and carrying capacity. This research was conducted between 29 August 2022 and 30 June 2023 and consists of a preliminary survey and main research activity. The study area encompasses eight selected areas: (1) Tegal Jarong, (2) Naga Island, (3) Samiah Fishing Spot, (4) Sabeulit Boating Spot, (5) Jemah Island, (6) Buaya Island, (7) Curug Mas, and (8) Cibunut Fishing Spot. The Tourism Suitability Index (TSI) was calculated for two tourism categories: Fishing and boating. The TSI result for the fishing category is ‘Conditionally Appropriate,’ while for boating activity is ‘Very Appropriate.’ The Total Tourism Carrying Capacity (TCC) for all study areas is about 13.818 visitors/day.